SENYAWA FENOLIK DARI DAUN HALBAN (Vitex pinnata Linn) SEBAGAI ANTIOKSIDAN - Mastura Mastura; Tonel Barus; Lamek Marpaung; Partomuan Simanjuntak (PROSIDING SEMINAR KIMIA, 2017)
Isolation and identification a phenolic compound from Aceh traditional medicinal plants “Halban” leaves (Vitexpinnata Linn) had been done. Isolation was carried out by extracted Halban leaves with methanol solvent, and then portioned with n-hexane, ethylacetate, and evaporated to gave n-hexane, ethylacetate and water extracts. Purification of ethylacetate was conducted with clumn chromatography (SiO2; (i). n-hexane-ethylacetate = 10 : 1 ~ 1 : 1 (ii). n-hexane-ethylacetate = 2 : 1 (iii). N-hexane-acetone = 1 : 1 to gave one pure compound. Identification of isolated compound by interpretation of Ultra violet (UV), Infra Red (IR), and Nuclear magnetic Resonance (1H- & 13C-NMR) spectra showed the compound is 4-hydroxyl methyl benzoate which has activity as antioxidant IC50 41.08 ppm. Keywords: Halban; Vitexpinnata Linn; verbenaceae; antioksidan; 4-hydroxyl methyl benzoate